2018
DOI: 10.1186/s12961-018-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

How is the use of research evidence in health policy perceived? A comparison between the reporting of researchers and policy-makers

Abstract: BackgroundThe use of health policy and systems research (HPSR) to inform health policy-making is an international challenge. Incorporating HPSR into decision-making primarily involves two groups, namely researchers (knowledge producers) and policy-makers (knowledge users). The purpose of this study was to compare the perceptions of Israeli health systems and policy researchers and health services policy-makers regarding the role of HPSR, factors influencing its uses and potential facilitators and barriers to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 47 publications
1
25
0
3
Order By: Relevance
“…We were able to identify perceived facilitators among men and women, such as the presence of structures linking researchers and target audiences, the investment of target audiences in KTE efforts and the presence of stable contacts among target audience. To some extent these ndings are in-line with studies conducted in other settings (28)(29)(30).…”
Section: Discussionsupporting
confidence: 89%
“…We were able to identify perceived facilitators among men and women, such as the presence of structures linking researchers and target audiences, the investment of target audiences in KTE efforts and the presence of stable contacts among target audience. To some extent these ndings are in-line with studies conducted in other settings (28)(29)(30).…”
Section: Discussionsupporting
confidence: 89%
“…Knowledge is an important source of wisdom and efficient actions in any organization [5]. Lack of synergy between knowledge and performance of health system is indeed a gap between knowledge and practice [6,7]. Promotion of public health requires attention to a knowledge-and evidence-based decision making system [8] and human development is possible by storing, using and sharing knowledge [9].…”
Section: Introductionmentioning
confidence: 99%
“…[53,54]) and previous studies indicate some enduring differences between policymakers and researchers in how they view the same research/policy interactions. For example, Ellen et al [55] found that policy-makers were more likely to emphasise contextual barriers to research use while researchers complained of communicative barriers. However, policy-makers may often understand research better than researchers understand policy [56].…”
Section: Future Directionsmentioning
confidence: 99%